(untitled) (Vallis Aurea, 2015)
Consequences of individual transport rapid development are a threat for modern cities and their population. Actually, transport problems in urban areas mostly derive from inadequate solutions of urban mobility by local transport systems. Majority of these problems are caused by extreme density of motor vehicles in urban areas. Increase of motor vehicles is a consequence of income increase and better standard of living. Accordingly, theoretical part of this study will investigate and elaborate on modern problems of urban transport, while the practical part of this work gives an overview of concrete solutions to some of the problems of urban transport on the example of the city of Rijeka in Croatia. Results of research also suggest guidelines for more efficient transport management in cities of similar size.